2019
DOI: 10.1109/tdsc.2017.2703626
|View full text |Cite
|
Sign up to set email alerts
|

A Scalable Approach to Joint Cyber Insurance and Security-as-a-Service Provisioning in Cloud Computing

Abstract: Abstract-As computing services are increasingly cloud-based, corporations are investing in cloud-based security measures. The Security-asa-Service (SECaaS) paradigm allows customers to outsource security to the cloud, through the payment of a subscription fee. However, no security system is bulletproof, and even one successful attack can result in the loss of data and revenue worth millions of dollars. To guard against this eventuality, customers may also purchase cyber insurance to receive recompense in the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…Recently, many studies analyzed the cyber risk insurance from a technology perspective. Security frameworks involving cyber risk insurance have been developed for specific IT systems, including computer networks (Fahrenwaldt, Weber, and Weske, 2018;Xu and Hua, 2019), heterogeneous wireless network (Lu, Niyato, Jiang, Wang, and Poor, 2018a), wireless cellular network (Lu et al, 2018b), plug-in electric vehicles (Hoang, Wang, Niyato, and Hossain, 2017), cloud computing (Chase, Niyato, Wang, Chaisiri, and Ko, 2019), and fog computing (Feng, Xiong, Niyato, Wang, and Leshem, 2018). Some studies considered the interplay between self-mitigation measures (i.e.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, many studies analyzed the cyber risk insurance from a technology perspective. Security frameworks involving cyber risk insurance have been developed for specific IT systems, including computer networks (Fahrenwaldt, Weber, and Weske, 2018;Xu and Hua, 2019), heterogeneous wireless network (Lu, Niyato, Jiang, Wang, and Poor, 2018a), wireless cellular network (Lu et al, 2018b), plug-in electric vehicles (Hoang, Wang, Niyato, and Hossain, 2017), cloud computing (Chase, Niyato, Wang, Chaisiri, and Ko, 2019), and fog computing (Feng, Xiong, Niyato, Wang, and Leshem, 2018). Some studies considered the interplay between self-mitigation measures (i.e.…”
Section: Related Workmentioning
confidence: 99%
“…There are also studies which took the insured's perspective and analyzed the security provisioning process using dynamic models. Chase et al (2019) developed a framework based on stochastic optimization to jointly provision cyber risk insurance and cloud-based security services across multiple time periods in cloud computing applications. Zhang and Zhu (2018) modeled the decisions on self-protections of the insured by a Markov decision process and investigated the problem of insurance contract design.…”
Section: Related Workmentioning
confidence: 99%
“…It only ensures secrecy of data to all other users who use the same server for data storage. Chase et al in 2019 [4] proposed technique for cyber insurance provisioning and security in cloud computing. It utilized stochastic optimization technique that provides optimally both services.…”
Section: Literature Surveymentioning
confidence: 99%
“…The numerical results showed that cyber insurance is an effective way to mitigate losses caused by cyberattacks for cloud providers. Alternatively, there are some other work introducing applications of cyber insurance to deal with cyber risks for cloud customers [10], [11]. The core idea of these papers is using stochastic programming to balance provisioning of security and insurance, even when future costs and risks are uncertain.…”
Section: Related Workmentioning
confidence: 99%